Effect of parity and type of lambing on performance and udder traits of Bandirma ewes - SEZENLER, TAMER; CEYHAN, AYHAN; YÜKSEL, MEHMET AKIF; ÖNALDI, ABDULLAH TANER; YILDIRIR, MESUT (The Indian Journal of Animal Sciences, 2016)
The objective of this study was to evaluate the effect of parity and lambing type on body condition score (BCS), live weight of ewes (LWE), daily milk yield (DMY), lambs growth performance and udder measurement of ewes during first 3 months of lactation in Bandirma ewes. Bandirma ewes (78) with healthy udders and their lambs (117 heads) were used. BCS of ewes was affected significantly by lambing types at first and third months of lactation, while lambing types were not significant in second month of lactation. Parity of ewes did not significantly affected BCS except third month of lactation which was significantly affected by parity. Effects of lambing types and parity of ewes were significant on BCS at first and third month of lactation. Live weight change of ewes was affected significantly by parity, while lambing types were not significant at first 3 months of lactation. There was a significant effect of parity on average daily milk yield at early lactation stage. Also lambing type had significant effect on DMY at first 2 months of lactation. DMY at third month of lactation were not affected by lambing types. Parity affected lambs growth performance in the first three months of lactation. No significant differences between lambing type and parity of ewes in udder measurement, except udder circumference (UC) measure which was significantly affected by parity and lambing types. The effects of parity of ewes were significant on udder circumference and udder width while the other udder traits were not significant. The effects of birth type of ewes were significant on udder width while the other udder traits were not significant. The positive and significant correlations were observed between udder circumference and udder width and daily milk yield in Bandirma sheep. Significant positive phenotypic correlations were determined between lambs live weight (LLW) and LWE, BCS and DMY, LLW and LWE, DMY and LWE. The results suggested that early stage of lactation of ewe’s can be feed supplemented with high energy or high protein for increasing milk production. The control of these physiological stages of ewe may be improved BSC and DMY, also growth performance of lambs. Hence, we recommend that early stage of lactation performance and udder measurements of ewes are to be taken into consideration for selection programme of Bandirma sheep.